Arbitrase Nasional Dengan Arbitrase Syariah: Suatu Kajian Perbandingan - Fadia Fitriyanti (Jurnal Media Hukum, 2013)
In the business world, many consideration that underlie the busuness actors to choose arbitration as dispute resolution efforts for dispute that will or they face.